Immersed in Media : Telepresence in Everyday Life. - Bracken, Cheryl Campanella (Routledge communication series., 2009)
""Over the next few decades, immersive media could fundamentally change the ways humans engage in entertainment, communication, and social interaction. The current volume takes a step towards understanding this potential paradigm shift, combining insights from pioneers of the field of 'presence' with bright young scholars who bring a new perspective."" --Jeremy Bailenson, Stanford University, USA ""This book provides an indispensable contribution to scholars in communication studies, computer science and psychology interested in the modes of being present in different media, and offers a caref.